The Application of Diagnostic Plots to Evaluate Water Flooding - Ratna Widyaningsih; Muhamad Zamzam Istimaqom; Hizballah Nidaulhaq; Atma Budi Arta (Journal of Petroleum and Geothermal Technology, 2020)
To analyze production optimization using waterflood, several types of diagnostic plots are needed to determine the response to using waterflood. If you have analyzed 1 plot, it is necessary to conduct a comprehensive analysis to evaluate its success rate by combining it using another plot analysis. The X-Min Field is a field that produces light oil and is managed by the Asset Optimization SLO North PT. Chevron Pacific Indonesia. This field was discovered in 1959 and started to be produced in 1966. Currently, 100 wells have been drilled with 37 active wells from 43 production wells, active injector wells are 18 out of 19, inactive wells 30, 4 wells have been plugged in, and there are 4 active wells that produce gas. The number of OOIPs in this field is 593 MMBO with cumulative production reaching 283.7 MMBO and Recovery Factor reaching 47.7%. In 2017 it was noted that the current production in December 2017 amounted to 5,374 BOPD / 121,264 BFPD or in other words the water cut reached 96.6%. Meanwhile, the amount of injection used to optimize this field is 144,103 BWIPD. Reservoirs in this field have 4 reservoirs namely Res-1, Res-2, Res-3, and Res-4 wherein each reservoir there are several grains of sand optimized using waterflood. There was 8 sand analyzed, including Sand Asyique, Sand Bajubaru, Sand Cemangad, Sand Emakpintar, Sand Fantamantap, Sand Gulungulung, Sand Harikita, and Special Sand. Closes the producer indicated premature water breakthrough. General recommendations given to various sands include adding or subtracting, both injectors and producers based on the response of each sand to water flooding.